Koklear implantlıların konuşma performansı Üzerinde FM Sistem Etkisi - (:unkn) unknown (My University, 2013)
0

Objective:This study aimed to examine the effects of Frequency Modulation (FM) system on cochlear implant recipients speech understanding in noisy environments. Material and Method: In this case study three cochlear implant users whose speech performance were evaluated good moderate and bad according to their monosyllabic word discrimination score in a quiet condition were tested to show the effects of FM system in a noisy condition. Threshold level (in dB HL) at 250, 500, 1000, 2000, 4000, 6000 Hz. and open set monosyllabic word discrimination scores were determined in quiet and in noisy conditions in three cases. Moreover, these tests were also repeated with FM system in noisy condition. Results: In noisy condition without FM, a decrease was found in hearing threshold levels and word discrimination scores for all three subjects. With FM system in noisy condition, hearing thresholds and word discrimination scores again increased as in quiet setting. Conclusion: FM system provides better speech understanding in noisy conditions for cochlear implant users by reducing the effects of noise, reverberation and distance. It shows that cochlear implant users have an advantage of better speech understanding in daily life with FM system.
The effects of FM system on cochlear implant recipients speech performance
Keywords: Genel ve Dahili Tıp